YIELD PERFORMANCE OF POTATO CULTIVARS AGAINST ARSENIC CONTAMINATION - Haque, Md. Nazmul; Ali, Md. Hazrat; Roy, Tuhin Suvra (Potato Journal, 2016)
Arsenic (As) contamination often affects the yield of potato tubers. In this study, therefore, yield contributing parameters of 14 potato cultivars in Bangladesh viz., ‘Diamant’, ‘Cardinal’, ‘Asterix’, ‘Granola’, ‘Lady Rosetta’, ‘Courage’, ‘BARI TPS-1’, ‘Meridian’, ‘Felsina’, ‘Laura’, ‘Quincy’, ‘Sagitta’, ‘Rumana’ and ‘Jam Alu’ were examined. The different levels of As had significant effect on most of the yield contributing characters of potato cultivars. All the parameters studied in this experiment were decreased with the increasing As levels except number of tubers/hill, non-marketable yield/plant, 28-45 mm and